Constructing Meaning Through Kid-Friendly Comprehension Strategy Instruction - Boyles, Nancy N. (Maupin House, 2004)
Nancy's comprehension and written response strategies give teachers the first-tier Response-to-Intervention (RTI) help they need to get students off to a great start! Good readers think about reading while they are reading. But how does a teacher teach students to apply comprehension strategies as they read? By applying the explicit teaching model to comprehension strategy instruction, Dr. Nancy Boyles offers teachers an easy, effective, and innovative approach to improve students' reading comprehension. Using her book -- rich with models, teacher-talk, and real-life examples -- teachers learn how to explicitly teach students to apply comprehension strategies competently while they read. And with Dr. Boyles' detailed lesson plans and templates, teachers can embed comprehension strategy instruction into guided, shared, and independent reading for both literacy and content-area instruction. Constructing Meaning shows teachers: A kid-friendly way to introduce and model a blended repertoire of comprehension strategies concurrently, so students practice strategies as readers actually use them: flexibly and as an integrated whole while reading. How to refine students' comprehension of fiction and informational text during shared, guided, and independent reading with focused lessons in specific strategy applications. How to monitor students' progress in reading comprehension and comprehension-strategy use through follow-up activities, rubrics with discrete assessment criteria, and questions that make kids think. Teachers can reproduce classroom-ready visual supports from the book or customize them from the included CD.
Keywords: Reading comprehension; Study and teaching (Elementary); dept.rdg; faculty_collection